(untitled) (Jurnal Destinasi Pariwisata, 2025)
The tourism industry 4.0 is a challenge for every country in the world to compete in increasing the role of human resources in the tourism industry through the digital era. Tourism village activists are required to have the ability in the field of Information and Communication Technology. This is necessary to meet the needs of an all-digital society and also to keep up with the times. This research discusses the efforts of Duda Timur Tourism Village in transforming management from conventional to digital. The descriptive method was used by the author in this research with a qualitative approach through literature studies and interviews. The result is that digital marketing, website creation and management as well as the utilization of the Sm@rtDesa application and the creation of virtual tours with a 3600 camera are part of the process of shifting Duda Timur Tourism Village from manual to digital management as a form of e-tourism implementation.